(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
: Innapropriate feeding practice is a feeding problem that is caused by incorrect eating behaviors that can impact a child’s nutritional status. In previous research by Rahmi in 2019, obtained from 110 respondents, 55.5% of children had difficulty eating, 21.8% of children with malnutrition, 25.5% of children with short nutritional status and 10% with thin nutritional status. underweight. Emotional is one of the things that affects children’s feeding patterns by 16.1%. This study aimed to analyze the relationship between parental emotional control and the application of feeding patterns in children aged 24-36 months in Kedungmundu Village. Quantitative method was applied with observational analytic design with cross sectional research design. The sample of this study were mothers with children aged 24-36 months in Kedungmundu Village, with the total of 68 people applied purposive sampling where the criteria included mothers who had children after 24-36 months in Kedungmundu Village as the main caregiver and exclude mothers who did not fill out the questionnaire completely. The data was analyzed using the Spearman Rank.The result obtained showed that the emotion control of parents were considered good (64.7%) and the diet of children was considered appropriate (76.5%) which in the Rank Spearman test obtained a p-value = 0.000 and r = 0.316 which indicated that there was a relationship accompanied by a positive correlation between parental emotional control and children’s diet with sufficient correlation strength. The results of the analysis show that the emotional factors of parents are closely related to the diet of children aged 24-36 months in Kedungmundu Village, where if the emotional factors of parents are said to be good, it will be in line with a good child’s eating pattern as well.